Consequences of “zombie-making” and generalist fungal pathogens on carpenter ant microbiota - Sophia Vermeulen (Current Research in Insect Science, 2025)
The bacterial microbiome of the ant Camponotus floridanus has been well characterized across body regions and maturation levels. However, potential effects of entomopathogens on the gut microbiome, and the fungal communities therein, are yet to be assessed. Additionally, the mycobiome remains often overlooked despite playing a vital role in gut ecology with potential implications for health and infection outcomes. We characterized the effects of two entomopathogens with different infection strategies on the gut micro- and mycobiota of C. floridanus over time; Ophiocordyceps camponoti-floridani and Beauveria bassiana. Specialist, ‘zombie-making’ O. camponoti-floridani fungi hijack the behavior of C. floridanus ants over three weeks, leading them to find an elevated position and fix themselves in place with their mandibles. This summiting behavior is adaptive to Ophiocordyceps as the ant transports the fungus to conditions that favor fruiting body development, spore production, dispersal, and transmission. In contrast, the generalist entomopathogen B. bassiana infects and kills the ant within a few days, without the induction of obvious fungus-adaptive behaviors. By comparing healthy ants with Beauveria- and Ophiocordyceps-infected ants we aimed to 1) describe the dynamics of the micro- and mycobiome of C. floridanus during infection, and 2) determine if the effects on gut microbiota are distinctive between fungi that have different infection strategies. While Beauveria did not measurably affect the ant host micro-and mycobiome, Ophiocordyceps did, especially for the mycobiome. Moreover, ants that were sampled during Ophiocordyceps-adaptive summiting behavior had a significantly different micro- and mycobiome composition compared to healthy controls and those sampled before and after manipulation took place. This suggests that the host microbiome might have a role to play in the manipulation strategy of Ophiocordyceps.